The quality of higher education as one of the philosophical foundations of education transformation XXI century: the European Context - Сухова, Н.М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The article is philosophical analysis of European approaches to assessments of the quality of higher education.